Mengukur efisiensi dan produktivitas Perusahaan Daerah Air Minum (PDAM) di Indonesia dari 2012-2016 - Sucia Miranti (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
Sufficiently clean water is accessible in Indonesia, where municipally-owned cooperation (BUMD) handles the management of the PDAM. It allows local governments authority over water management in their administrative districts. This organization is responsible for maintaining the region's water supply while earning income from water business operations. However, this effort is not deemed effective since having many PDAMs results in inadequate water quality, low water distribution, and even financial losses. However, the assumption lacks factual evidence as they are not assessed alongside the government audit. To analyze the inefficiencies of water supply services and the productivity growth of PDAMs from 2012 to 2016, this research proposes to use a non-parametric technique, namely data envelopment analysis (DEA) and Malmquist Index Calculation, respectively. The research findings reveal significant inefficiencies among PDAM from various regions in Indonesia. It was found that PDAMs outside Java performed better than those in Java; thus, PDAMs need policy intervention. The operations of larger municipal PDAMs should be restructured to increase productivity. There was no TFP growth (TFPCH) in PDAMs, evidenced by the reduction in pure technical (TECH) and scale efficiency change (SECH). In addition, the positive technological adjustment (TECCH) did not significantly improve efficiency. Regarding the increase in the number of PDAMs resulting from technological improvement, productivity was primarily due to technological advancement.